2020
DOI: 10.1111/apa.15596
|View full text |Cite
|
Sign up to set email alerts
|

A shorter breastfeeding duration in late preterm infants than term infants during the first year

Abstract: Aim Little attention has been paid to breastfeeding late preterm (LPT) infants. This study compared breastfeeding, worries, depression and stress in mothers of LPT and term‐born infants throughout the first year. We also described factors associated with shorter breastfeeding duration of LPT infants. Methods This longitudinal cohort study of the mothers of singleton infants—129 born LPT and 277 born at term—was conducted at Landspitali—The National University Hospital of Iceland, which has the country's only n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Although a broad definition of breastfeeding was used during the literature search and selection of papers, positive experiences of feeding the infant were only described when the mother breastfed at breast in all papers. One reason for this could be that in many settings the norm and goal is to feed the infant directly at breast [ 5 , 8 ]. When mothers do not achieve this goal but instead feed the infant by alternative means, i.e., a bottle, the overall experience becomes negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a broad definition of breastfeeding was used during the literature search and selection of papers, positive experiences of feeding the infant were only described when the mother breastfed at breast in all papers. One reason for this could be that in many settings the norm and goal is to feed the infant directly at breast [ 5 , 8 ]. When mothers do not achieve this goal but instead feed the infant by alternative means, i.e., a bottle, the overall experience becomes negative.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that even small changes in the prevalence of breast milk feeding may result in significant changes in health, healthcare costs, and economic productivity for preterm infants and their mothers [ 2 ]. Despite the overwhelming evidence of the value of breast milk for mothers and their preterm and/or LBW infants, there are wide variations in the initiation and duration rates of feeding breast milk [ 3 5 ], where preterm infants have shown to have a shorter breast milk feeding duration compared to term infants [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the qualitative phase was to help explain and elaborate on the results obtained in the first phase [26,27]. According to this mixed-method study design, the first phase consisted of an analysis of the quantitative data on all twins in a longitudinal cohort survey of mothers of LPT (34 0 / 7 to 36 6 / 7 weeks) infants and term (37 0 / 7 to 41 6 / 7 weeks) infants [28,29]. In the second phase, the qualitative phase, issues from the first phase and literature were explored in individual semi-structured interviews with another population of mothers of LPT twins.…”
Section: Methodsmentioning
confidence: 99%
“…In this cohort study, maternal-infant separation was found to be most common in late preterm newborns (LPT)(34 + 0 –36 + 6 ), who had a low exclusive breastfeeding rate after discharge from the hospital, only 45 of 359 (12.5%) late premature infants were exclusively breastfed 6 months after discharge from the hospital, far below the WHO target of 50% exclusive breastfeeding rate at 6 months [ 27 ]. Several studies have revealed lower rates of breastfeeding initiation and shorter breastfeeding duration in LPT newborns when compared to term infants [ 37 , 38 ], despite the recognized short- and long-term effects of LPT births, as well as the mother and baby health benefits of breastfeeding [ 37 ]. These differences in breastfeeding could be due to a variety of factors, including maternal medical difficulties, delayed lactogenesis and infant clinical abnormalities.…”
Section: Discussionmentioning
confidence: 99%